2002
DOI: 10.1046/j.1528-1157.43.s.5.27.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Opioid Peptide and Muscarinic Receptors in Human Epileptogenic Neocortex: An Autoradiography Study

Abstract: Summary: Purpose:The main goal of the present study was to evaluate possible alterations in opioid peptide and muscarinic receptors in human neocortical epileptic focus and the surrounding area removed from patients with pharmacologically resistant epilepsy and epilepsy secondary to cerebral lesion by tumor or other causes.Methods: In vitro quantitative autoradiography experiments were carried out to label , ␦, and muscarinic receptors of neocortical epileptic focus and surrounding area obtained from patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…Neuronal plasticity evidences the response of a circuit, a neurotransmitter or a receptor that is modified as a result of different factors or altered processes. Herein it is shown that muscarinic receptor changed promptly after stimulus (BIC administration), a finding in line with the observation that this receptor is enhanced in the human epileptic focus at early times following seizures through activity-dependent mechanisms [ 35 ].…”
Section: Discussionsupporting
confidence: 77%
“…Neuronal plasticity evidences the response of a circuit, a neurotransmitter or a receptor that is modified as a result of different factors or altered processes. Herein it is shown that muscarinic receptor changed promptly after stimulus (BIC administration), a finding in line with the observation that this receptor is enhanced in the human epileptic focus at early times following seizures through activity-dependent mechanisms [ 35 ].…”
Section: Discussionsupporting
confidence: 77%
“…Eventually, the irritative zone zone serves as a control condition, compared with the epileptogenic region of the same patient. However, studies indicate that both regions present significant changes, suggesting an increased excitatory influence in the epileptic focus and decreased inhibitory neurotransmission in the irritative zone 132 . Indeed, the irritative zone increases vascularity, microlesions, and marked activation of mitogen‐activated protein kinase and cAMP‐response element‐binding protein (MAPK/CREB, a signaling pathway involved in synaptic plasticity) 133 .…”
Section: Discussionmentioning
confidence: 99%
“…However, studies indicate that both regions present significant changes, suggesting an increased excitatory influence in the epileptic focus and decreased inhibitory neurotransmission in the irritative zone. 132 Indeed, the irritative zone increases vascularity, microlesions, and marked activation of mitogen‐activated protein kinase and cAMP‐response element‐binding protein (MAPK/CREB, a signaling pathway involved in synaptic plasticity). 133 Previous studies that focused on the human brain with epilepsy revealed a high expression of long noncoding RNA (lncRNAs) genes involved in synaptic plasticity, a situation that correlated with the interictal spiking activity.…”
Section: Discussionmentioning
confidence: 99%
“…The autoradiography experiments were carried out on adjacent sections thaw-mounted on gelatincoated slides according to the procedures described previously. [17][18][19] Experimental conditions for mu, delta and nociceptin autoradiography are summarized in Table 2. The brain sections were initially washed.…”
Section: Tissue Preparation and Histopathologymentioning
confidence: 99%